Sistem Informasi Presensi Karyawan Berbasis Web Menggunakan Model RAD - Anisah, A; Supardi, S; Kirana, Chandra; Mayasari, Melati Suci; Perkasa, Eza Budi; Irawadi, Syafrul (LPPM STIKOM Tunas Bangsa, 2024)
Employee attendance in a company is a vital aspect of Human Resources Management (HRM) system that helps ensure employee discipline and it also can be used to facilitate payroll management. This attendance allows the company to take necessary actions to improve workplace discipline. This research aims to develop a web-based employee attendance information system using the Rapid Application Development (RAD) model and the system development method using an Object-Oriented methodology with the help of Unified Modelling Language (UML) tools. Thus, this attendance information system can assist the company or organization take easy the HR department's task of monitoring employee attendance in real-time, enhancing the efficiency of attendance-related administrative processes, and providing accurate and detailed reports on employee attendance patterns within an organization or company.